Assessing the Capabilities of Additive Manufacturing Technologies for Coral Studies, Education, and Monitoring - Gutierrez-Heredia, Luis; Keogh, Colin; Reynaud, Emmanuel G. (Frontiers in Marine Science, 2018)
Abstract Additive manufacturing, better known as 3D printing is becoming an easily accessible method to produce 3D objects ranging from medical devices to jet plane parts. However, this implies the creation of an accurate 3D digital model by Computer Assisted Design (CAD) or direct acquisition of a 3D model as well as a correct understanding of the various 3D printing technologies available with their pros and cons. Here, we present a method for editing and printing of 3D models of coral colonies for the generation of accurate and enhanced 3D models suitable for research and education. This is a follow-up from other papers where 3D scanning was performed on fresh coral samples from field trips and coral skeletons from museum collections using different imaging techniques (multi-image photogrammetry and Micro CT scanning). 3D scans of colonies and samples of Turbinaria sp., Leptoseris incrustans, Oulophyllia crispa, Echinopora sp., Siderastrea savignyana and Platygira daedalea were used to produce multi-material and multi-scale 3D prints. Moreover, we studied the best practices for the 3D printing processes, and potential technologies most suitable for specific attributes in this practice. Additionally, we show the innovative application of 3D printed inert reactive corals able to indicate environmental changes, along with insights into the potential uses for the proposed method and related systems in biological fields and sharing with an online community.